In Search of a Dramatic Equilibrium : Was the Armenian Dram Overvalued? - Oomes, Nienke (IMF Working Papers; Working Paper ;, 2009)
This papers estimates the equilibrium exchange rate for Armenia using three different approaches: the purchasing power parity (PPP) approach, the behavioral equilibrium exchange rate (BEER) approach, and the external sustainability (ES) approach. All three approaches suggest that the dram was overvalued by about 20-30 percent prior to the devaluation of the dram in March 2009.